Fundamental History of Russian Folklore Studies of the XXth Century (Филологический класс, 2012)
The article reviews T.G. Ivanova's monograph History of Russian Folklore Studies of the XXth Century: 1900-first half of 1941. Greater attention is paid to the problem of realizing immanent regularities in the development of Folklore Studies in the first half of the XXth century.